THE CONCEPT OF MORAL RESPONSIBILITY IN KANT PHILOSOPHY AND ITS RELEVANCE TO TEACHER PROFESSIONAL ETHICS - Afni Rosalina; M Manugeren; Efendi Barus (BASIS (Bahasa dan Sastra Inggris), 2026)
This study aims to examine the concept of moral responsibility in the moral philosophy of Immanuel Kant and its relevance to teacher professional ethics. Kant’s ethical theory emphasizes that the moral value of an action is determined by intention and adherence to duty rather than consequences. This research employs a qualitative descriptive approach using library research. The data sources include Kant’s primary philosophical texts and relevant literature on educational ethics. Data are collected through document analysis and analyzed using interpretative and thematic analysis to identify key ethical principles and their application in teaching practice. The findings show that the categorical imperative encourages teachers to treat students as ends in themselves, promoting fairness, respect, and integrity in classroom interactions. Teachers are positioned as moral agents responsible not only for knowledge transmission but also for students’ character development and dignity. However, challenges such as administrative pressures, curriculum demands, and social changes may hinder the consistent application of Kantian ethics in practice.mIn conclusion, integrating Kant’s moral philosophy into teacher professionalism supports a more humanistic and morally grounded educational environment, while highlighting the need for reflective practice and institutional support.